Vendors selling dried chillies at wholesale markets - Mumbai Archive Project Team (Jio Institute, 2024)
Typically, one might purchase spices from vendors selling dried chillies at wholesale marketplaces. The masala's bright red colour and pungent flavour are derived from Kashmiri chillies used to make the base, though other varieties may also be used.